Academic Achievement and Economic Attainment: Reexamining Associations Between Test Scores and Long-Run Earnings - Tyler W. Watts (SAGE Publishing, 2020)
The current article reexamines the correlation between achievement test scores and earnings by providing new evidence on the association between academic skills and measures of adult earnings assessed when participants were in their 30s, 40s, and 50s. Results suggest that math and reading scores are strong predictors of economic attainment throughout participants' careers, but these associations may also be sensitive to controls for other characteristics-including measures of the early family environment, general cognitive functioning, and socioemotional skills. Although these associations demonstrate the likely importance of achievement skills in determining labor market productivity, the variability in the achievement-to-earnings correlation suggests that researchers should apply caution when using the correlation to project the long-run effects of educational interventions.